Frontiers and recent developments on supercapacitor's materials, design, and applications: Transport and power system applications. (February 2023) - Bhat, Md. Yasir; Hashmi, S.A.; Khan, Majad; Choi, Daniel; Qurashi, Ahsanulhaq
Abstract: In this ever increasing energy-dependent globe, energy storage devices perform an important role in reducing dependency on fossil fuels. Supercapacitors end-to-end with rechargeable batteries can be used to afford supplementary power required for various purposes, e.g., electric vehicles and hybrid electric vehicles. Supercapacitors have attracted significant interest due to their rate of charge-discharge, long cyclability, and high power-density. However, there are multiple challenges that need to be resolved, of which the most urgent are the research and development of active electrode materials and electrolytes that need to be studied using new materials with desirable properties for energy device applications. This review provides an in-depth analysis of various areas that cover the state-of-art progress of supercapacitors and their applications in various fields, including transport and power systems. Firstly, we provide a brief introduction to important details of supercapacitors, and their types, followed by an in-depth discussion of various active electrodes based on carbons, conducting polymers, and transition metal-oxides, and then presenting the comprehensive studies of various electrolytes consisting of liquid and polymer-based electrolytes with their different classes and remarkable electrochemical properties. The electrode and electrolyte materials of supercapacitors are discussed with respective electrochemical analyses tabulated based on fundamental and ultimately targeting various properties and desirable behavior. We discuss new findings on supercapacitor mechanisms and designs followed by providing a comprehensive overview focusing on the new active electrode materials for supercapacitors. The descriptive demonstration of new devices for supercapacitors and micro-supercapacitors designs with their different types is presented. The supercapacitor applications in various transport and power fields are also touched upon systematically. Finally, the challenges and future opportunities of this promising supercapacitor field for advanced and emerging applications are included. Highlights: Fundamentals of supercapacitor and micro-supercapacitors are critically reviewed. Current state-of-the-art supercapacitor work is summarized. Frontiers and opportunities for materials design is envisaged.